2021
DOI: 10.1186/s12893-021-01318-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. open feeding jejunostomy insertion in oesophagogastric cancer

Abstract: Background Jejunal feeding is an invaluable method by which to improve the nutritional status of patients undergoing neoadjuvant and surgical treatment of oesophageal malignancies. However, the insertion of a feeding jejunostomy can cause significant postoperative morbidity. The aim of this study is to compare the outcomes of patients undergoing placement of feeding jejunostomy by conventional laparotomy with an alternative laparoscopic approach. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Both lower thoracic spinal nerves and celiac plexus carries nociceptive somatic and visceral afferent inputs of the corresponding areas which these innervates [16]. Feeding jejunostomy involves mini laparotomy through a midline incision between T7 to T9 dermatomes in the anterior abdominal wall followed by enterotomy and fixation of a feeding tube inside the jejunal loop [17]. Hence, we have used SC TAP block to block the T6 to T10 spinal nerves to facilitate anterior abdominal wall manipulation and CP block to facilitate bowel handling during feeding jejunostomy.…”
Section: Resultsmentioning
confidence: 99%
“…Both lower thoracic spinal nerves and celiac plexus carries nociceptive somatic and visceral afferent inputs of the corresponding areas which these innervates [16]. Feeding jejunostomy involves mini laparotomy through a midline incision between T7 to T9 dermatomes in the anterior abdominal wall followed by enterotomy and fixation of a feeding tube inside the jejunal loop [17]. Hence, we have used SC TAP block to block the T6 to T10 spinal nerves to facilitate anterior abdominal wall manipulation and CP block to facilitate bowel handling during feeding jejunostomy.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with advanced unresectable gastric cancer with dyspepsia, a laparoscopic jejunostomy may be an option for treatment. In a retrospective study, it was reported that there were fewer postoperative complications with laparoscopic jejunostomy than with the open approach [13] . Especially in advanced gastric cancer, the results of the JLSSG0901 study showed that laparoscopic surgery is not inferior to open surgery; thus, the percentage of laparoscopic gastric cancer surgery is expected to increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to open FJ, laparoscopic Witzel technique for FJ has limited reports in the literature and has not been discussed widely as a standalone procedure. Furthermore, LFJ by Stamm technique is also preferred at many centers but is associated with many complications [1,4]. Hence, there is a definite need to discuss the technical aspect of LFJ and its outcomes in detail.…”
Section: Introductionmentioning
confidence: 99%